AVI Media business plan - Chauhan, Shailendre (2009)
Preschool children in a modern lifestyle are getting more global, tech savvy and multilingual. Whether it is a pressure from parents or society kids are expected to perform from an early age. Television is very much part of children’s’ lifestyle all over the world and the time spend watching TV is on the rise. Though there are arguments on both the sides, various researches suggests that television remains one of the most influential communication medium in children’s emotional, social and cognitive development. Television can be an interactive and fun medium, contributing to a positive and constructive development in children. This dissertation takes an entrepreneurial approach by looking into a sociological and business aspect of culture. Divided into two parts, first part looks into existing research on the subject followed by quantitative research into culture awareness in preschool children. Second part of dissertation is a business plan that explores entrepreneurial opportunities in cultural convergence. The dissertation research focuses on communicating cultural awareness to preschool children. Business plan is for a new start up Media Company to create an animation television (TV) program for preschool children with the aim to communicate cultural awareness in them. Tara, the global kid is an animation series targeted at preschool children from AVI media private limited based in Nottingham, UK. The company is a new start-up venture by professionals from within the media industry and business. The company is looking to tap into the lucrative children’s media industry in UK market, with the aim to expand in Europe, US and Middle East Asia markets. With an introduction of an ethnic (Indian) character via an edutainment program for TV and other audio visual platforms, the company offers growth potential for investors and stakeholders, making this an attractive investment in a dynamic industry. The program is aimed at children from all ethnicity, race and background, but keeping the Asian culture at core, giving children an entertaining glimpse into the Asian culture (mainly India, Pakistan and Bangladesh) in UK. According to Office of National Statistics the size of the minority ethnic population was 4.6 million in 2001 or 7.9 per cent of the total population of the United Kingdom. In Great Britain the minority ethnic population grew by 53 per cent between 1991 and 2001. Half of the total minority ethnic population were Asians of Indian, Pakistani, Bangladeshi or other Asian origin. AVI Media is requires an initial investment of £ 48,000 to launch the business.